2011
DOI: 10.1097/rli.0b013e3182034fc2
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Hemodynamics in Patients With and Without Repair of Aortic Coarctation

Abstract: Alterations in aortic hemodynamics after CoA repair are not limited to the specific region of repair, but can be found in the entire aorta. The presented findings highlight the systemic nature of the disease and the need for a systemic diagnostic approach which can be provided by flow-sensitive 4D PC MRI. Furthermore, valuable additional insights on the hemodynamic consequences of coarctation have been shown that may help understanding secondary complications such as restenosis, aneurysm formation, and arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 36 publications
0
70
1
Order By: Relevance
“…In MFS, in vivo identification of such secondary flow patterns may help to identify patients at risk for the development of typical vascular complications. Similar to the findings in bicuspid aortic valve or aortic coarctation, the visualization of altered hemodynamics may facilitate the understanding of the pathomechanisms leading to aneurysm formation and onset of dissection (10,16).…”
mentioning
confidence: 77%
“…In MFS, in vivo identification of such secondary flow patterns may help to identify patients at risk for the development of typical vascular complications. Similar to the findings in bicuspid aortic valve or aortic coarctation, the visualization of altered hemodynamics may facilitate the understanding of the pathomechanisms leading to aneurysm formation and onset of dissection (10,16).…”
mentioning
confidence: 77%
“…48,57 Helical flow can be regarded as the rotational motion of blood oriented normal to the mainstream of blood flow during its passage of the artery. 29,101 In the helical flow, the streamlines in the lumen of arteries demonstrate the shape of helices and those on the cross sections of the arteries exhibit secondary rotations. The special geometry and the helical flow in the aorta are possibly a typical example of 'form follows function' in the circulation, which secures the human ascending aorta to be insusceptible to atherosclerotic plaque formation.…”
Section: Introductionmentioning
confidence: 99%
“…We added zero mean Gaussian noise to the velocity field in each direction (x, y, and z directions) with four different variances (2.5, 5, 7.5, and 10%) of the peak velocity, which was set to 1 m/s. Subsequently, we applied our method to estimate the vorticity vector field, which was then compared with the theoretical values obtained from the derivative value of Equation [13]. The equation for vorticity vector x can be written as…”
Section: Robustness and Convergence Analysismentioning
confidence: 99%
“…Studies based on 3D cine PC-MRI performed on phantom data have revealed that vortex and helical flow can induce vessel wall injury and vascular remodeling (7,(9)(10)(11). Additionally, other studies have demonstrated that standard surgical procedures induce local and global hemodynamic changes of the treated section, altering the secondary flow patterns, which could lead to the reappearance of the pathology and the need for re-intervention (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%